Managing IT professionals in the Internet age - Yoong, Pak, 1945-; Huff, Sidney Laurence (Hershey, PA : Idea Group Pub. (an imprint of Idea Group Inc.), 2006)
'This book explores the ways in which the work life of IT professionals - from the perspectives of both the individual IT worker, and managers of such workers - has had to change and adapt to the Internet Age'--Provided by publisher
Keywords: Information technology -- Management; Personnel management